CE/BZA effects on bone and quality of life in European postmenopausal women: a pooled analysis. (2nd September 2016) - Hadji, P.; Ryan, K. A.; Yu, C.-R.; Mirkin, S.; Komm, Barry S.
Abstract: Objectives: To evaluate the efficacy of conjugated estrogens/bazedoxifene (CE/BZA) on bone mineral density (BMD), bone turnover markers (BTM), and menopause-specific quality of life (MENQOL) in European women. Methods: Data through 12 months were pooled from two double-blind, randomized, controlled trials in non-hysterectomized postmenopausal women who received CE/BZA or placebo. Women from European study sites with evaluable BMD ( n = 60), BTM ( n = 56), and MENQOL questionnaire ( n = 236) data were included and compared with 1523 women from US study sites ( n = 730 with evaluable data for bone outcomes). Results: At month 12, CE 0.45 mg/BZA 20 mg and CE 0.625 mg/BZA 20 mg, respectively, significantly improved BMD (adjusted difference vs. placebo) in lumbar spine (2.5%, 2.9%; both p ≤ 0.011) and total hip (1.7%, 2.2%, both p ≤ 0.002), significantly improved serum BTMs (osteocalcin: –31.1%, –33.1%; C-telopeptide: –48.5%, –36.8%) vs. placebo (osteocalcin: 6.7%, C-telopeptide: 4.2%; all p < 0.001), and significantly improved MENQOL vasomotor function scores (–2.1, –2.2) vs. placebo (–0.7; both p < 0.001). No significant treatment × subpopulation interactions were observed for any of the outcomes. Conclusions: Twelve-month CE/BZA treatment prevented bone loss and improved vasomotor function in European postmenopausal women. Findings were similar to those in the subpopulation of women enrolled at US study sites.